Evaluating serum cyclooxygenase-2 and vascular endothelial growth factor as biomarkers for endometriosis severity in reproductive-age women - Aslam, Aga; Rajuddin, Rajuddin; Munizar, Munizar; Rusnaidi, Rusnaidi; Hasanuddin, Hasanuddin (Narra J, 2026)
Endometriosis affects approximately 10–15% of reproductive-age women and up to 70% of those with chronic pelvic pain, with diagnosis typically relying on invasive laparoscopy with histopathological confirmation. Cyclooxygenase-2 (COX-2) and vascular endothelial growth factor (VEGF) are central mediators of the inflammatory and angiogenic pathways underpinning endometriosis pathogenesis, making them promising candidates for non-invasive biomarkers. This study aimed to analyze the correlation between serum COX-2 and VEGF concentrations and endometriosis severity to evaluate their potential utility as non-invasive biomarkers. A cross-sectional study was conducted among women with confirmed endometriosis at Dr. Zainoel Abidin General Hospital in Banda Aceh, Indonesia, in 2025. Peripheral blood samples were collected preoperatively, and serum COX-2 and VEGF concentrations were quantified using ELISA. Endometriosis severity was classified according to the American Society for Reproductive Medicine staging system. Correlation analyses were performed to assess associations between biomarker levels and disease stage, and diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis to determine the area under the curve (AUC) values, optimal cut-off points, sensitivity, and specificity. Twenty-eight patients were included, with the mean COX-2 and VEGF levels being 1.16±1.28 ng/mL and 266.50±72.91 pg/mL, respectively. VEGF demonstrated a strong and statistically significant correlation with endometriosis staging (r=0.744, p<0.001), while COX-2 showed a limited correlation that did not reach statistical significance (r=0.367, p=0.055). The ROC analysis further highlighted VEGF’s superior diagnostic performance, with an AUC of 0.975 (95%CI: 0.926–1.000, p<0.001) compared with COX-2 (AUC 0.734; 95%CI: 0.518–0.950, p=0.057). The optimal VEGF threshold of 221 pg/mL yielded 90% sensitivity and 100% specificity, whereas the COX-2 threshold of 0.675 ng/mL provided 80% sensitivity and 62.5% specificity. These findings indicate that VEGF is a highly promising non-invasive biomarker for assessing endometriosis severity and may support the development of improved diagnostic approaches for endometriosis management.